Factors Affecting People of Using Nicknames on Facebook Account Instead of Using their Real Names - Rasool, Izaddin A. (Humanities Journal of University of Zakho, 2017)
Currently, the world we live-in go through many changes by way of different means and rates. These changes have an impact on the society (in general) and into an individual (in particular). One of these changes happens of human relationships, particularly through Internet communication, especially through social network sites. Thus, social networking sites have rapidly become one of the most popular tools for social interaction and information exchange. A social network, which has become popular recently, does not know any geographical boundaries and does not have a specific time to be used either positively or negatively. Today, social networks sites have changed the way of human communications to great extent. Communication with or within universities, Newspapers, media channels, libraries, Museums, Markets, banks, software and electronic games of such facilities can be easily available for many people around the world and for different purposes. This means that anyone can get everything/anything, at everywhere/anywhere at any time without any boundaries restriction. In addition, from an unpretentious beginning as a platform, social networks sites like “Facebook” plays an important role for this present generation for sharing images, personal information, joining groups of friends, writing common interests, and supplementing traditional social interactions. Hence, this brings changes to many different fields. This study aims in revealing the factors that people using nicknames on Facebook account and why they are not free to use their real name. The study is based on quantitative research method, using a questionnaire in the Kurdistan region of Iraq. An online-based survey was generated from snowball sampling. There were 84 male respondents and 23 female respondents. The study mainly found that, social factors such as distrust society member or suspicion another gender are the main factors that force Kurdish person not to use his/her real name on Facebook account.